Supply-side contribution to the lack of PBF impact on unmet need for family planning in Burkina Faso: Christopher Hertler. (25th October 2022) - Hertler, C; Lohmann, J; Koulidiati, JL; Robyn, PJ; Somda, SMA; De Allegri, M; Brenner, S
Abstract: Background: In 2020, about one in four women in Burkina Faso faced an unmet need for family planning (FP). Between 2013 and 2017, Burkina Faso implemented a performance-based financing (PBF) program to improve primary health care service provision (including FP) at rural health centers. Our prior work revealed that PBF did not lead to a reduction in unmet need for FP, in spite of FP being an explicitly targeted service. Our current study assesses supply-side factors that have likely contributed towards this lack of effect at population level, by examining changes in facility-based indicators relevant to the provision of FP induced by PBF. Methods: We used facility-based survey data from 406 PBF and 117 control facilities collected before and after the PBF implementation. To compare changes in FP service provision, we examined changes in a number of relevant indicators including: a. the types of FP methods offered by facilities; b. trainings received by different FP providers; and c. available stocks of modern contraceptives. We relied on a difference-in-differences (DID) regression model to estimate the impact of PBF on these indicators. Results: We observed a significant positive impact on the number of staff qualified to provide injectables, implants and IUDs (effect size 0.47, p 0.003) as well as the number of facilities offering IUDs (effect size 0.28, p 0.016) and a significant reduction in the number of facilities experiencing stock-outs of female condoms (effect size -0.09, p 0.007) and implants (effect size -0.03, p 0.042). Conclusions: Given the significant positive impacts on the number of qualified staff, facilities providing IUDs and a reduction in stock-outs of female condoms and implants attributable to the PBF intervention without showing signs of negative effects on the indicators measured supply-side factors might not have been the main reason for the lack of effect of the PBF program on unmet need for FP. Key messages:  Supply-side factors might not have been the main reason for the lack of effect of the PBF program on unmet need for FP.  Further research is needed to explore other potential underlying reasons.